Baccharis coridifolia Poisoning in Water Buffalo (Bubalus bubalis) in the North of the Province of Corrientes, Argentina - Lértora, Walter J.; Negrette, Marcial S. (Brazilian Journal of Veterinary Pathology, 2015)
Eight of 57 water buffalo (Bubalus bubalis) died after grazing 30 days on 38-hectare pasture contaminated with Baccharis coridifolia in the north of the Province of Corrientes (northeastern Argentina). Most were found dead, others showed depression, anorexia, diarrhea, incoordination of movements and collision against fences. The conditions that caused the poisoning were overgrazing, poor pasture and lack of aversion to the consumption of Baccharis coridifolia. Gross findings included necrotic rumenitis, necrotic-hemorrhagic abomasitis, necrotic-hemorrhagic enteritis and marked brain edema. The histopathological findings were necrosis of the epithelium of the mucosa of the forestomachs, necrosis and hemorrhage in mucosa of the small intestine, necrosis of lymphocytes in lymph follicles in spleen and thymus and vasogenic brain edema. The lesions, except for brain edema, are typically reported in cattle intoxicated by Baccharis coridifolia. Vasogenic brain edema is not described in any animal species naturally or experimentally intoxicated with this plant; this change may be due to direct toxic effect of Baccharis coridifolia that cause vascular injury or was a secondary injury.